Techno-functional, pasting and microstructural characteristics of flour obtained from three Bambara groundnut varieties as affected by dehulling and malting - Mpho Edward Mashau; Thakhani Takalani; Shonisani Eugenia Ramashia; Oluwaseun Peter Bamidele (International Journal of Food Properties)
This research aimed to examine the influence of dehulling and malting (120 h) on the functional, thermal, pasting, and microstructural characteristics of flours from three Bambara groundnut (BGN) varieties (cream, brown, and red). Dehulling and malting significantly enhanced (p < .05) the oil absorption capacity, bulk density, swelling power, and solubility of flours in all BGN varieties. Malting significantly increased (p < .05) the water absorption capacity, whereas dehulling reduced it. Nonetheless, the true density, Carr index, and Hausner ratio of the BGN flours were reduced. Dehulling significantly enhanced (p < .05) the L* value, whereas the a* value of the BGN flours was reduced. The opposite trend was observed for malted BGN flour. Both traditional methods increased the yellowness of the BGN flours. The breakdown and setback viscosity of the processed flours significantly increased, whereas the trough, final viscosity, and peak time decreased. Furthermore, dehulling significantly increased (p < .05) the peak viscosity, while malting reduced it. Dehulling and malting increased the onset and peak temperatures of the BGN flours, whereas the end temperature and enthalpy decreased. Malting decreased the relative crystallinity of the BGN flours. The XRD patterns of the BGN flours did not show significant variations, and similar peaks were observed in the FTIR spectra. Both methods altered the morphology of the BGN flours. The findings of this study support dehulling and malting as promising processing methods for industrial applications of BGN flour, with potential for wide applications beyond other legume products.